The Research Field of Islamic Bank: A Hybrid Systematic Literature Review And Bibliometric Analysis - Rachman Zuhri, Arif; Erwindiawan; Abdusyakur, Muhammad Zulfan (Likuid Jurnal Ekonomi Industri Halal, 2025)
Abstract This study aims to map the research landscape of Islamic bank by examining its intellectual structure, thematic evolution, and global distribution. The research addresses the growing academic interest in Shariah-compliant finance and identifies key areas of theoretical contribution and practical relevance. Using a hybrid methodology that combines a Systematic Literature Review (SLR) and bibliometric analysis, this study analyzed 1,132 articles retrieved from the Scopus database up to June 12, 2025. The PRISMA framework guided the article selection, and VOSviewer was employed to visualize citation patterns, author networks, and keyword co-occurrences. This research presents a novel synthesis of 20 years of Islamic banking literature by categorizing research trends, highlighting top contributing authors, institutions, and countries, and exposing underexplored areas such as fintech integration, customer behavior, and regional regulatory practices. The findings show a significant growth in Islamic banking publications, particularly in Indonesia and Malaysia. Key themes include corporate governance, financial performance, and institutional comparisons with conventional banks. The most frequent keywords were “Islamic Banks” (330), “Islamic Banking” (185), and “Corporate Governance” (63), confirming the field's conceptual maturity and revealing emerging research gaps. This study confirms that Islamic banking remains a vibrant and evolving field of research. It offers strategic insights for scholars and practitioners, establishing a foundation for future inquiry and policy innovation in global Islamic finance. These insights have both theoretical implications by identifying maturing and emerging themes and practical relevance in guiding future policymaking, regulatory design, and investment strategies in Islamic financial markets.